Supportive care against correcting protein-energy malnutrition in patients with generalized gastrointestinal cancer - O. M. Petrova; O. N. Lipatov; L. N. Kudryashova (Креативная хирургия и онкология, 2023)
Introduction. A decrease in nutrition of cancer patients affects all vital functions of the body, which is, according to numerous studies, typical of patients with gastrointestinal disturbances.Materials and methods. The study was set out to investigate the effect of correcting protein-energy malnutrition on the symptoms manifestation, including pain, fatigue, sleep disorder, poor appetite, nausea, vomiting, constipation and diarrhea in patients with generalized forms of gastrointestinal cancer. The study involved questionnaire method applied prior to the study and three months after. Three groups, equivalent in terms of selection criteria, participated in the study. For this purpose, the study participants were given nutridrink compact protein and omega-3 polyunsaturated fatty acid.Results and discussion. This study found out that timely nutritional support contributes toward reducing the negative symptoms of cancer and, when combined with supportive care and pain management, leads to significantly better results in terms of improving quality of life.Conclusion. Timely nutritional support has a positive effect on reducing the negative symptoms associated with cancer (pain, fatigue, sleep disorder, poor appetite, nausea, vomiting, constipation and diarrhea), and, along with supportive care and pain management, improves the quality of life more significantly.